Detection of bacterial DNA from central venous catheter removed from patients by next generation sequencing: a preliminary clinical study - Ken-ichi Okuda; Yutaka Yoshii; Satomi Yamada; Akio Chiba; Ippei Hironaka; Seiji Hori; Katsuhiko Yanaga; Yoshimitsu Mizunoe (BMC, 2018)
Abstract Background Catheter-related infection (CRI) is one of the serious challenges in clinical practice. This preliminary clinical study aimed to examine whether next-generation sequencing (NGS) targeting 16S rDNA, which was PCR-amplified directly from the tip of a central venous catheter (CVC), can be used to identify causative pathogens in CRI, compared to the culture method. Methods Hospitalized patients, from whom a CVC had just been removed, were prospectively enrolled and divided into the CRI-suspected and routine removal groups. DNA was extracted from the sonication fluid of CVC specimens derived from patients. For analysis of bacterial composition by NGS, the V3-V4 fragments of bacterial 16S rDNA were PCR-amplified, followed by index PCR and paired-end sequencing on an Illumina MiSeq device. Conventional culture methods were also performed in the CRI-suspected group. Results Of CVCs collected from the 156 enrolled patients (114 men; mean age 65.6 years), a total of 14 specimens [nine out of 31 patients suspected with CRI and five out of 125 patients without infection symptoms (routine removal group)] were PCR-positive. In five patients with definite CRI, Staphylococcus was the most frequently detected genus by NGS (4/5 specimens), although no pathogens were detected by NGS in the one remaining specimen. The genera identified by NGS were consistent with those from conventional culture tests. There was high agreement between NGS and the culture method in the CRI-suspected group, with sensitivity and specificity values of 80.0% and 76.9%, respectively; meanwhile, the false-positive rate of NGS was as low as 4.0% in the routine removal group. Moreover, several genera, besides the genus identified by culture test, were detected in each patient with definite CRI and surgical site infection (SSI). Additionally, in one patient with SSI, Enterococcaceae were detected not only by NGS but also by abdominal abscess drainage culture. Conclusions NGS targeting 16S rDNA was able to analyze the bacterial composition of CVC specimens and detect causative pathogens in patients with CRI and was therefore suggested as a promising diagnostic tool for CRI.